In Vitro effects of tamoxifen on equine neutrophils. (February 2017) - Borlone, C.; Morales, N.; Henriquez, C.; Folch, H.; Olave, C.; Sarmiento, J.; Uberti, B.; Moran, G.
Abstract: Neutrophils participate in innate immunity as the first line of host defense against microorganisms. However, exacerbated neutrophil activity can be harmful to surrounding tissues; this is important in a range of diseases, including allergic asthma and chronic obstructive pulmonary disease in humans, and equine asthma (also known as recurrent airway obstruction (RAO). Tamoxifen (TX) is a non-steroidal estrogen receptor modulator with effects on cell growth and survival. Previous preliminary studies showed that TX treatment in horses with induced acute pulmonary inflammation promoted early apoptosis of blood and BALF neutrophils, reduction of BALF neutrophils, and improvement in animals' clinical status. The aim of this study was to evaluate the in vitro effect of TX on functional tests in equine peripheral blood neutrophils. Chemotaxis, respiratory burst production and phagocytosis assays were performed on neutrophils isolated from peripheral blood samples from 10 healthy horses. Results showed that IL-8 stimulated cells decrease their chemotactic index when treated with TX (1 and 10 μM). Respiratory burst production was also dampened after treatment with TX. In conclusion, these results confirm that tamoxifen has a direct action on equine peripheral blood neutrophils. However, more in vivo and in vitro studies are required to fully understand the mechanisms of action of TX on neutrophils, in order to elucidate if it can be used as treatment in disorders such as allergic asthma in humans and horses. Highlights: Studies showed that tamoxifen treatment in horses with acute pulmonary inflammation promoted improvement in animals' clinical status. We evaluated the effect of tamoxifen on equine peripheral blood neutrophils We did chemotaxis, respiratory burst and phagocytosis assays Tamoxifen has a direct action over neutrophilic functions (chemotaxis and respiratory burst) These results suggest that the effect of TX could explain the clinical improvement in horses with acute lung inflammation